청소년들의 시간관리능력이 대면 및 비대면 학습몰입에 미치는 영향: 부모 학습관여의 조절효과 - 김은진(Eun-Jin Kim); 정구철(Goo-Churl Jeong) (한국콘텐츠학회 논문지, 22(5), 2022)
The purpose of this study was to verify the moderating effect of parental learning involvement in the effect of adolescents' time management ability on face-to-face and non-face-to-face learning flow. The participants were 363 middle and high school adolescents, and data were collected through an online survey. The main statistical analysis methods were ANOVA, correlation analysis, and regression analysis. The major findings were as follows. First, learning flow was significantly higher in the face-to-face class than in the non-face-to-face class. Second, there was a statistically significant positive correlation among time management ability, parental involvement in learning, and learning flow. Third, in the effect of time management ability on face-to-face learning flow, the moderating effect of parental learning involvement was statistically significant. Fourth, in the effect of time management ability on non-face-to-face learning flow, the moderating effect of parental learning involvement was statistically significant. In other words, the higher the positive parental involvement in learning, the stronger the effect of adolescents' time management ability on learning flow. Finally, the importance of positive parental involvement for the improvement of adolescents' learning flow and methods of enhancing time management ability were discussed. 본 연구의 목적은 청소년들의 시간관리능력이 대면 및 비대면 학습몰입에 미치는 영향에서 부모 학습관여의 조절효과를 검증하는 것이다. 연구 대상자는 중·고등학교 청소년 363명이었고, 온라인 설문조사를 통해 자료를 수집하였다. 주요 통계 분석 방법은 분산분석, 상관관계분석 및 회귀분석이었다. 연구결과, 첫째, 비대면 수업보다 대면 수업에서 학습몰입이 유의하게 높았다. 둘째, 시간관리능력, 부모 학습관여 및 학습몰입 간에 유의한 정적 상관관계가 있었다. 셋째, 시간관리능력이 대면 학습몰입에 미치는 영향에서 부모 학습관여의 조절효과는 유의하였다. 넷째, 시간관리능력이 비대면 학습몰입에 미치는 영향에서 부모 학습관여의 조절효과는 유의하였다. 즉, 부모의 긍정적 학습관여가 높아질수록 청소년들의 시간관리능력이 학습몰입에 미치는 영향을 더욱 강하게 하였다. 마지막으로 청소년들의 학습몰입의 증진을 위한 부모의 긍정적 관여의 중요성과 시간관리능력 증진 방법을 논의하였다.